Temporal ontology-mediated queries and first-order rewritability: A short course - Ryzhikov, V; Walega, P; Zakharyaschev, M (Springer, 2020)
We discuss recent attempts to extend the ontology-based data access (aka virtual knowledge graph) paradigm to the temporal setting. Our main aim is to understand when answering temporal ontology mediated queries can be reduced to evaluating standard first-order queries over timestamped data and what numeric predicates and operators are required in such reductions. We consider two ways of introducing a temporal dimension in ontologies and queries: using linear temporal logic LTL over discrete time and using metric temporal logic MTL over dense time.